Interpretasi Hadis QadhÄâ€™ Puasa Mayit menurut Metodologi Yusuf al-Qaradawi - Husna, Himmayatul; Khamim, Khamim (El Nubuwwah Jurnal Studi Hadis, 2025)
This study explores the divergent interpretations among Muslim scholars regarding prophetic traditions (á¸¥adÄ«ths) associated with the legal obligation of qadhÄâ€™ (paying back the missed fasting) on behalf of deceased individuals. The disagreement emerges from the categorization of ritual worship (Ê¿ibÄdah) into physical, financial, or combined acts, raising jurisprudential debates over whether such actsâ€”especially fastingâ€”can be fulfilled by legal proxy. Within Islamic legal discourse, some jurists argue that the guardian (walÄ«) must perform the missed fasts of the deceased, while others opine that paying fidyah (compensatory feeding of the poor) is sufficient. These divergent views stem from differing hermeneutical readings of several á¸¥adÄ«ths, including those reported by Ê¿Ä€Ê¾ishah and Ibn Ê¿AbbÄs, which appear contradictory in literal interpretation. This research employs a qualitative methodology using a library-based (literature review) approach, analyzing hadith and fiqh texts across multiple legal schools (madhÄhib). The interpretive framework of YÅ«suf al-QaradÄwÄ« is utilized to critically assess and reconcile these texts, incorporating key principles such as jamÊ¿u al-aá¸¥ÄdÄ«th (harmonization), tarjÄ«á¸¥ (preference of evidence), and asbÄb al-wurÅ«d (contextual background of narration). The study finds that al-QaradÄwÄ«â€™s comprehensive approach to hadith interpretation allows for a more coherent understanding of scholarly disagreements and offers a rational foundation for legal rulings across schools. It concludes that methodological engagement with prophetic texts is essential in developing inclusive, adaptable, and well-reasoned Islamic legal judgments in the context of modern jurisprudential needs.